"THE RELATIONSHIP BETWEEN PARKINSON'S DISEASE AND TYPE 2 DIABETES MELLITUS: CLINICAL FEATURES AND PATHOPHYSIOLOGICAL MECHANISMS" (World Bulletin of Public Health, 2023)
Parkinson’s disease (PD) and type 2 diabetes mellitus (T2DM) are two widely prevalent chronic diseases that significantly affect the quality of life of patients. In recent years, the number of studies dedicated to analyzing the interaction between these diseases has been growing. In particular, clinical and neurological features of Parkinson's disease in the context of T2DM are being studied. This review article presents the results of an analysis of modern research on this topic
Keywords: Parkinson's disease; Type 2 diabetes mellitus; Neurological features